Designing P. aeruginosa synthetic phages with reduced genomes - Diana P. Pires (Nature Portfolio, 2021)
Abstract In the era where antibiotic resistance is considered one of the major worldwide concerns, bacteriophages have emerged as a promising therapeutic approach to deal with this problem. Genetically engineered bacteriophages can enable enhanced anti-bacterial functionalities, but require cloning additional genes into the phage genomes, which might be challenging due to the DNA encapsulation capacity of a phage. To tackle this issue, we designed and assembled for the first time synthetic phages with smaller genomes by knocking out up to 48% of the genes encoding hypothetical proteins from the genome of the newly isolated Pseudomonas aeruginosa phage vB_PaeP_PE3. The antibacterial efficacy of the wild-type and the synthetic phages was assessed in vitro as well as in vivo using a Galleria mellonella infection model. Overall, both in vitro and in vivo studies revealed that the knock-outs made in phage genome do not impair the antibacterial properties of the synthetic phages, indicating that this could be a good strategy to clear space from phage genomes in order to enable the introduction of other genes of interest that can potentiate the future treatment of P. aeruginosa infections.